2017
DOI: 10.3389/fonc.2017.00185
|View full text |Cite
|
Sign up to set email alerts
|

Propensity Score Matched Comparison of Intensity Modulated Radiation Therapy vs Stereotactic Body Radiation Therapy for Localized Prostate Cancer: A Survival Analysis from the National Cancer Database

Abstract: PurposeNo direct comparisons between extreme hypofractionation and conventional fractionation have been reported in randomized trials for the treatment of localized prostate cancer. The goal of this study is to use a propensity score matched (PSM) analysis with the National Cancer Database (NCDB) for the comparison of stereotactic body radiation therapy (SBRT) and intensity modulated radiation therapy (IMRT) for organ confined prostate cancer.MethodsMen with localized prostate cancer treated with radiation dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Eight studies compared different conventional EBRT doses ranging from 68 Gy to >80 Gy [34,73,75,80,81,89,90,101], with increasing doses over the years due to the introduction of conformal and then intensity modulated RT (IMRT). One NRS compared 3D-conformal RT (70)(71)(72)(73)(74) to IMRT (78)(79)(80)(81)(82) showing better survival outcomes in the IMRT-group for BFFS, OS and CSS) [90].…”
Section: Ebrt -Trials Of Dose Fractionation and Field Sizementioning
confidence: 99%
“…Eight studies compared different conventional EBRT doses ranging from 68 Gy to >80 Gy [34,73,75,80,81,89,90,101], with increasing doses over the years due to the introduction of conformal and then intensity modulated RT (IMRT). One NRS compared 3D-conformal RT (70)(71)(72)(73)(74) to IMRT (78)(79)(80)(81)(82) showing better survival outcomes in the IMRT-group for BFFS, OS and CSS) [90].…”
Section: Ebrt -Trials Of Dose Fractionation and Field Sizementioning
confidence: 99%
“…Numerous retrospective/single institution experiences have included highrisk patients from 7.4 to 65.9% of their patient cohorts, with variable total doses (32-40 Gy in 5 fractions) and ADT use (4,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In addition, a large National Cancer Database study did not find a difference in overall survival between SBRT and conventionally fractionated patients when propensity-matched high-risk subpopulations of Gleason score 8+ or PSA >10 (19). Despite potential selection bias, results are promising with 5-year BFFR between 70 and 80% in most series.…”
Section: Discussionmentioning
confidence: 99%
“…In a rapidly changing research landscape, SBRT has demonstrated similar toxicity profiles and non-inferior disease control compared with conventionally fractionated radiotherapy in many phase I/II trials (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), a landmark phase III trial (18), a National Cancer Database propensity matched analysis (19), and a recently completed systematic review and meta-analysis (20). Included in these trials were intermediate and high-risk patients; however, not all studies provided biochemical or overall survival data as stratified by risk group and high-risk patients made up only a minority of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In both trials at 20 years followup, WW versus RP was associated with higher mortality among men at intermediate risk but not low-or high-risk disease. We identified six reports of two unique randomized controlled trials (RCTs) 12,[42][43][44][45][46] and nine reports of four unique non-RCTs 24,27,[47][48][49][50][51][52][53] that compared AS/AM to other therapies. Serious or critical risk of bias (ROB) precluded the inclusion of non-RCTs in the analysis.…”
Section: Variation In Outcomes By Participant or Tumor Characteristicsmentioning
confidence: 99%